2014
DOI: 10.3109/00207454.2014.980906
|View full text |Cite
|
Sign up to set email alerts
|

Soluble or soluble/membrane TNF-± inhibitors protect the brain from focal ischemic injury in rats

Abstract: Tumor Necrosis Factor-alpha (TNF-α) is an immunomodulatory and proinflammatory cytokine implicated in neuro-inflammation and neuronal damage in response to cerebral ischemia. The present study tested the hypothesis that anti-TNF-α agents may be protective against cerebral infarction. Transient focal ischemia was artificially induced in anesthetized adult male Wistar rats (300-350 g) by middle cerebral artery occlusion (MCAO) with an intraluminal suture. TNF-α function was interfered with either a chimeric mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…We have shown that CD4 + T‐cell‐derived IL‐21 is a major contributor of reperfusion damage following tMCAO as CD4 + T cells from IL‐21‐deficient mice do not cause the same levels of ischaemic damage compared with CD4 + T cells from wild‐type mice when transferred intravenously into T‐cell‐deficient mice . Other cytokines such as IL‐1 β , TNF‐ α , and particularly IL‐23 have also been shown to influence T cells following stroke indirectly …”
Section: Lymphocytes Encompass Adaptive Immune‐mediated Responses Folmentioning
confidence: 97%
See 1 more Smart Citation
“…We have shown that CD4 + T‐cell‐derived IL‐21 is a major contributor of reperfusion damage following tMCAO as CD4 + T cells from IL‐21‐deficient mice do not cause the same levels of ischaemic damage compared with CD4 + T cells from wild‐type mice when transferred intravenously into T‐cell‐deficient mice . Other cytokines such as IL‐1 β , TNF‐ α , and particularly IL‐23 have also been shown to influence T cells following stroke indirectly …”
Section: Lymphocytes Encompass Adaptive Immune‐mediated Responses Folmentioning
confidence: 97%
“…103 Other cytokines such as IL-1b, TNF-a, and particularly IL-23 have also been shown to influence T cells following stroke indirectly. 104,105 Recently, there has been a lot of excitement for the potential role of T regulatory (Treg) cells for protection against stroke damage. Liesz et al showed that transfer of Foxp3 + T cells into T-cell-deficient mice was protective and that Treg cells were present surrounding ischaemic brain areas at 7, 14 and 30 days following 30-min tMCAO.…”
Section: Lymphocytes Encompass Adaptive Immunemediated Responses Follmentioning
confidence: 99%
“…Moreover, it may be that certain compounds, in certain conditions, do not necessarily have to pass the BBB to reach therapeutic effects. For example, in rat MCAO models for cerebral ischemia beneficial effects were reported upon intraperitoneal injection of etanercept [124,125]. However, it may be that etanercept could enter the brain via disruptions in the BBB, induced by the MCAO [124].…”
Section: Targeting Tnfrs As Treatment For Neurodegenerative Disordersmentioning
confidence: 99%
“…As reviewed by Pan and Kastin (2007), TNF-α was shown to have both detrimental and beneficial effects in stroke [121]. Several studies reported that inhibition of TNF-α (e.g., by etanercept, a human TNFR2-IgG Fc fusion protein) reduces infarct size and neuroinflammation [122][123][124][125], while, on the other hand, complete knockout of both TNFRs increases the sensitivity for stroke and aggravates neuronal damage [5]. Moreover, in stroke in vitro and animal models, pre-treatment with TNF-α (which models ischemic preconditioning) mediates neuroprotective effects after ischemia [126,127].…”
Section: Ischemic Strokementioning
confidence: 99%
“…In addition, such drug can prevent damage from oxidation of the cell membrane and inhibit brain edema and cerebral infarction due to cerebral hemorrhage [8]. Tumor necrosis factor α (TNF-α) is a proinflammatory cytokine involved in neural inflammation and corresponding neuronal injury due to cerebral ischemia [9]. Interleukin (IL)-8 is a chemokine that not only induce chemotaxis of target cells but also facilitate transfer of neutrophils, eosinophils, and T cells to infection sites [10].…”
Section: Introductionmentioning
confidence: 99%